UK consensus statement on the use of plerixafor to facilitate autologous peripheral blood stem cell collection to support high‐dose chemoradiotherapy for patients with malignancy. Issue 1 (20th June 2017) - Douglas, Kenneth W.; Gilleece, Maria; Hayden, Patrick; Hunter, Hannah; Johnson, Peter R. E.; Kallmeyer, Charlotte; Malladi, Ram K.; Paneesha, Shankara; Pawson, Rachel; Quinn, Michael; Raj, Kavita; Richardson, Deborah; et al.
Abstract: Plerixafor is a CXC chemokine receptor (CXCR4) antagonist that mobilizes stem cells in the peripheral blood. It is indicated (in combination with granulocyte‐colony stimulating factor [G‐CSF]) to enhance the harvest of adequate quantities of cluster differentiation (CD) 34+ cells for autologous transplantation in patients with lymphoma or multiple myeloma whose cells mobilize poorly. Strategies for use include delayed re‐mobilization after a failed mobilization attempt with G‐CSF, and rescue or pre‐emptive mobilization in patients in whom mobilization with G‐CSF is likely to fail. Pre‐emptive use has the advantage that it avoids the need to re‐schedule the transplant procedure, with its attendant inconvenience, quality‐of‐life issues for the patient and cost of additional admissions to the transplant unit. UK experience from 2 major centers suggests that pre‐emptive plerixafor is associated with an incremental drug cost of less than £2000 when averaged over all patients undergoing peripheral blood stem cell (PBSC) transplant. A CD34+ cell count of <15 µl −1 at the time of recovery after chemomobilization or after four days of G‐CSF treatment, or an apheresis yield of <1 × 10 6 CD34+ cells/kg on the first day of apheresis, could be used to predict the need for pre‐emptive plerixafor.